Developing a baseline measurement tool for environmental impact a case study on a selected clothing company - Felipe, Angelica N.; Gripal, Leynard L. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The objective of this research was to develop a baseline measurement tool for the environmental impact of the retailing of clothing based on its logistic requirements as an answer to the problem of how environmental impact of clothing retailing can be measured. The study went through a three-step process in order to achieve this. Beginning with document analysis, specifically focusing on the Global Reporting Initiative's (GRI) Sustainability Reporting Guidelines, indicators identified were Energy, Materials, and Products and Wastes. The researcher then conducted interviews with key informants from the logistics department of a selected clothing company in order to describe logistic activities of the clothing company with respect to the three indicators. Finally, the researcher designed a tool that the company can use to measure the environmental impact of their retailing activities in each of the core indicators previously identified. The tool was verified by the key informants from the selected company for its coverage and validated by an Environmental Scientist specializing in Environmental Impact Assessment as an objective third party in order to confirm the effectiveness and integrity of the measurement tool. The resulting baseline measurement tool was designed specifically for the selected clothing company, and is therefore most effective when used by that company. Researcher recommends further study on developing environmental impact measurement tools for the entire supply chain - from manufacture of fibers up to the post-consumer impact. In addition, the subsequent environmental impact control and monitoring tool with the ultimate objective of reducing the entire industry's environmental impact is also recommended.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing trade -- Environmental aspects; Clothing factories -- Environmental aspects